Dark Patterns dalam Digital Marketing: Etika dan Dampaknya terhadap Loyalitas Konsumen - I Nyoman Susipta (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of the research is to identify and classify dark-patterns used in digital marketing analysis, perceptions of the ethics of dark-pattern use, examine the impact of dark-patterns on consumer loyalty, and provide ethical understanding as a basis for preparing responsible digital marketing strategies. The method used is a quantitative approach with a survey method through primary data obtained directly from respondents through the distribution of questionnaires designed to measure their experiences and perceptions of the use of dark patterns in the context of digital marketing. Meanwhile, secondary data was obtained through a literature study that included scientific journals, academic articles, industry research reports, and related documents that discussed key concepts such as dark patterns, digital marketing ethics, and consumer loyalty. The study concluded that dark patterns with practices such as forced continuity, hidden costs and countdown timers reduce consumer trust in brands and lead to a decrease in consumer loyalty. Dark patterns can only offer short-term benefits in terms of conversions and sales, but their long-term impact decreases consumer loyalty to both products and brands.